Excluding tortured confessions in the People's Republic of China: A long March towards the eventual abolition of torture? - Jiang, Na (International journal of law, crime and justice, 2018)
Since its ratification of the United Nations' Convention against Torture and Other Cruel, Inhuman or Degrading Treatment or Punishment (CAT) in 1988, China has enacted many laws and rules in order to prohibit torture. But torture still happens, and tortured confessions continue to influence trials, as numerous wrongful convictions demonstrate. This study aims to examine why there are persistent practices of forced confession in China and to identify the roots of torture in China's current criminal justice system in order to mend the remaining flaws. Currently, the definition of torture used in China is too limited in scope, and not all illegally obtained evidence can be excluded even by law. In practice, courts focus on remedying wrongful convictions caused by torture in a narrow sense and are not totally in line with international standards. Even defence lawyers are charged with separate crimes and tortured to confess sometimes, seriously detrimental to fairness and justice. So, more institutional restraints on banning police torture are necessary, in spite of many reform measures that have already been taken. Legislative revisions on the scope of torture and institutional reforms on supervising police interrogations are needed at the very least. All lawyers should be immune from criminal investigations relating to their work during their defence against tortured confession in all cases.